Current knowledge on the Cuvette Centrale peatland complex and future research directions - Biddulph, George Elliot; Bocko, Yannick Enock; Bola, Pierre; Crezee, Bart; Dargie, Greta C.; Emba, Ovide; Georgiou, Selena; Girkin, Nicholas T.; Hawthorne, Donna; Jovani-Sancho, A. Jonay; Kanyama, Joseph; Mampouya, Wenina Emmanuel; et al. (C I R A D, 2021)
The Cuvette Centrale is the largest tropical peatland complex in the world, covering approximately 145,000 km2 across the Republic of Congo and the Democratic Republic of Congo. It stores ca. 30.6 Pg C, the equivalent of three years of global carbon dioxide emissions and is now the first trans-national Ramsar site. Despite its size and importance as a global carbon store, relatively little is known about key aspects of its ecology and history, including its formation, the scale of greenhouse gas flows, its biodiversity and its history of human activity. Here, we synthesise available knowledge on the Cuvette Centrale, identifying key areas for further research. Finally, we review the potential of mathematical models to assess future trajectories for the peatlands in terms of the potential impacts of resource extraction or climate change.
Keywords: tropical peatland; carbon storage; greenhouse gas emissions; palaeoecology; biodiversity; Anthropocene; Democratic Republic of Congo